Influence of mixed solvents on characteristics and photoluminescence of GdVO4: Eu3+nanophosphors synthesized by solvothermal method - Watcharapong Pudkon (2018)
© 2016 by American Scientific Publishers. GdVO4:Eu3+nanoparticles were synthesized by a solvothermal method at 200°C for 24 h, followed by calcination at 600°C for 3 h. The effects of mixed solvents (water:methanol, water:ethanol, water:ethylene glycol and water:glycerol) on purity, crystallinity, size and agglomeration behavior of the GdVO4:Eu3+nanoparticles were investigated. The products, characterized by powder X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and energy dispersive X-ray spectroscopy (EDS), were indexed as pure GdVO4with tetragonal structure. Field emission scanning electron microscope (FESEM) and transmission electron microscope (TEM) images revealed that the synthesized powders composed of spherical nanoparticles with diameters of about 15-40 nm. The difference in the characteristics of the synthesized nanoparticles could be related to the properties of the solvents used in the present work. The GdVO4:Eu3+nanoparticles synthesized using the mixed solvent of water:glycerol was smaller in size with soft agglomerations offering the highest photoluminescence (PL) emission intensity. Whereas, the PL intensity of the nanoparticles synthesized using water:ethylene glycol was lower than those of the others probably due to the existence of some defects in the crystals.